Process control of robotic tile laying based on position-based impedance and fuzzy-adaptive contact force control - Huixing Zhou; Shun Wang; Chongwen Xu; Haoyu Li (Journal of Intelligent Construction)
Construction robots have garnered attention with the rapid development of construction automation. Such tiling robots can effectively improve the construction quality and efficiency. To enhance the quality of robotic tile laying, a control method based on position servo and position impedance was proposed herein. To improve the full filling rate, the robot improved the full reduction rate of tile laying using the effective vibration from an eccentric vibrator. Experimental results showed that the proposed method could effectively improve the tile laying quality. The results of this study will promote the application of robotic tile laying to engineering and provide a reference for the improvement in the quality of robotics in construction.